Mucosal colonization of Mannheimia haemolytica capsular and adhesin mutants in cattle - Anna K. Goldkamp; Harish Menghwar; Carly Kanipe; Robert E. Briggs; Bradley O. Chriswell; Eduardo Casas; Michael L. Clawson; Fred M. Tatum; Rohana P. Dassanayake (Microbiology Spectrum)
ABSTRACT Mannheimia haemolytica (Mh) is a normal inhabitant of the upper respiratory tract of ruminants and is associated with bovine respiratory disease. Polysaccharide capsule and surface adhesins are suggested to function in adherence and colonization of M. haemolytica to the mucosa of the upper respiratory tract. M. haemolytica serotype 1 mutant strains containing deletions of either the capsule biosynthetic gene cluster (∆cap) or putative adhesin genes (∆adh123) were created using a temperature-sensitive plasmid and tested for colonization in a calf challenge model. Two treatment groups were used in the study: Sham-Mh-BHV-1 (SMB; intranasal administration of uninfected cell culture lysate/supernatant [sham; S] 4 days before intranasal M. haemolytica inoculation, and intranasal inoculation of bovine-herpesvirus-1 [BHV-1] 20 days post-Mh) and BHV-1-Mh-Sham (BMS; intranasal inoculation of BHV-1 4 days before intranasal Mh inoculation and intranasal sham administration 20 days post-Mh). A mixture of wild-type M. haemolytica parent strain, ∆cap, and ∆adh123 mutants was included in the Mh inoculum. Animals were observed for clinical signs and nasal colonization for approximately 7 weeks. The ∆adh123 mutant and parent strain colonized the nasopharynx, whereas the ∆cap mutant was not detected after 1 day post-inoculation. The ∆adh123 mutant colonized the nasopharynx at significantly higher levels (P < 0.0001) compared to wild type. Higher colonization of ∆adh123 was also found in palatine tonsils. These findings suggest a requirement of capsule in long-term colonization and an advantage for ∆adh123 in colonization over the parent strain.IMPORTANCEUnderstanding the colonization dynamics of Mannheimia haemolytica is crucial for developing effective prevention and treatment strategies for bovine respiratory disease (BRD), a significant cause of economic loss in the cattle industry. This study highlights the role of capsular polysaccharide and surface adhesins in nasopharyngeal colonization. These findings demonstrate that the deletion of putative surface adhesins leads to enhanced colonization compared to the wild-type strain, while mutants containing a deletion of the capsule biosynthetic gene cluster failed to establish long-term colonization. These results suggest that targeting bacterial adhesion mechanisms could influence bacterial persistence and immune response, offering potential avenues for controlling BRD.